Dunhuang was not isolated: examples such as 'Master Yixing sets up earth-wheel lamps' and others from Yunnan. Issue 1 (2nd January 2022) - Hou, Chong
ABSTRACT: Buddhist ritual procedures such as the setting up of Sky-wheel Lamps 天輪燈 and Earth-wheel Lamps 地輪燈 were previously only seen in the Dunhuang manuscript (D2074, BD15147, G015, etc.) and its related materials. It turns out that these procedures can also be found in the ordinance and ritual ( keyi 科儀) manuscript used by Azhali 阿吒力 monks in Dali 大理, as well as in Song text Shuilu yi 水陸儀 [Water-land Rituals], and in the Dali manuscript Zhufo pusa Jin'gang deng qiqing 諸佛菩薩金剛等啟請. Three different types of Choutian xiedi manuscripts collected recently from Yunnan all share similar contents and contain phrases such as 'Master Yixing sets up earth-wheel lamp' (一行禪師設地燈), which corresponds to the Dunhuang manuscript Yixing dashi shi shijie dilun dengfa . This chain of evidence demonstrates that the Dali Buddhist tradition in Nanzhao 南詔 as well as the Azhali tradition were all components of Chinese Buddhism. On the other hand, these findings provide new examples for the important reference value of Yunnan Chinese Buddhism as for the study of post-Tang Chinese Buddhism.